New Insights into Probabilistic Thinking: A Study of Cognitive Styles and Probability Problem-Solving among Masculine Male Students - Supratman; Enda budi rahaju; I Ketut Budayasa (Research Collaboration Community (Rescollacom), 2026)
This study investigated a new insight into the probabilistic thinking of male mathematics education students with Field-Independent cognitive style. One student with masculine male and a Field-Independent cognitive style (MLI) based on the GEFT test and a gender questionnaire, while also considering mathematical ability assessed through UTBK SBMPTN questions. From 20 students with medium-level mathematical ability, MLI was chosen to participate in a probability problem-solving test conducted at the Faculty of Teacher Training and Education, Universitas Sembilanbelas November Kolaka. This research employed a descriptive qualitative method with a case study design. The results indicate that MLI's probabilistic thinking is highly proficient. Based on Polya’s four problem-solving stages, MLI effectively identified given information, recorded data accurately, and answered in a structured manner, although he did not explicitly write the combination formula or binomial distribution. In the